PREDICTORS AND COMPONENTS OF INPATIENT ASTHMA HOSPITAL COST: A CROSS SECTIONAL STUDY - AFRIDI, SS; BASIT, A; NAEEM, M; TARIQ, M; ULLAH, S; MAQBOOL, M; IQBAL, N (Biological and Clinical Sciences Research Journal, 2024)
Asthma, a chronic respiratory condition, continues to impose a significant economic burden on healthcare systems worldwide. Objective: The main objective of the study is to find the predictors and components of inpatient asthma hospital cost. Methods: This cross-sectional study was conducted at a tertiary care hospital from January 2024 to June 2024. Data were collected from 245 patients suffering from asthma. Patients were selected based on the International Classification of Diseases (ICD) codes related to asthma documented in their medical records. Patients aged >18 years with complete medical and billing records available were included in the study. Results: The results show that gender did not significantly affect hospital costs, with males averaging $7,400 and females $7,000 (p = 0.12). Age was a significant predictor, as older patients (65+ years) incurred higher costs ($9,800) compared to younger groups (p < 0.01). Socioeconomic status also impacted costs, with lower-income patients averaging $8,100 compared to $6,200 for higher-income patients (p < 0.05). Age (65+ years) increased costs by $1,800 in univariate analysis and by $1,500 in multivariate analysis (p < 0.01). Asthma severity had the strongest effect, with severe cases adding $5,500 in univariate analysis and $4,800 in multivariate analysis (p < 0.001). Comorbidities increased costs by $4,000 univariately and $3,500 in multivariate models (p < 0.01).Conclusion: It is concluded that asthma severity, comorbidities, and socioeconomic status are the primary predictors of inpatient asthma hospital costs.